2020
DOI: 10.1101/2020.07.05.20146589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 national lockdown in Morocco: impacts on air quality and public health

Abstract: On the 20th April 2020, the end date of the first strict lockdown period in Morocco, 2 403 410 cases of the corona Virus were confirmed globally. The number of Morocco confirmed cases attended 2990, while 12 746 were suspected and 143 deaths were recorded. Due to the pandemic of coronavirus disease 2019 worldwide and in Morocco, almost all avoidable activities in the country were prohibited since the kingdom announced activities reduction on March 16, 2020 and then general lockdown with reduced industrial acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Thus, COVID-19 pandemic has proved to be a 'blessing in disguise' which can help earth to revive and improve air quality [35] which has been supported by many research studies conducted in different parts of the world [1,5,6,9,12,13,23,28,32,33,35,36,42,43,48,55,57,58,61,63,69,75]. Further it has been found that places where the air pollution was high, deaths rate due to COVID-19 also enhanced [13,23,32,48,69,75]. In India, the concentration of sulphur dioxide between April 2019 and April 2020 decreased by around 40% [19] as shown in Fig.…”
Section: Review Of Studies Linked With Air Pollution and Morality During Covid-19mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, COVID-19 pandemic has proved to be a 'blessing in disguise' which can help earth to revive and improve air quality [35] which has been supported by many research studies conducted in different parts of the world [1,5,6,9,12,13,23,28,32,33,35,36,42,43,48,55,57,58,61,63,69,75]. Further it has been found that places where the air pollution was high, deaths rate due to COVID-19 also enhanced [13,23,32,48,69,75]. In India, the concentration of sulphur dioxide between April 2019 and April 2020 decreased by around 40% [19] as shown in Fig.…”
Section: Review Of Studies Linked With Air Pollution and Morality During Covid-19mentioning
confidence: 98%
“…Tian et al (2020) stated that longterm exposure to PM 2.5 is directly linked with COVID-19 mortality [69]. Najmi et al (2020) in their study compared the air quality status in Marrakech and Casablanca, two large cities from Morocco during the lockdown and before the pandemic and found drop in air pollutants benefitting the health of the humans and reducing the rate of morality [48].…”
Section: Review Of Studies Linked With Air Pollution and Morality During Covid-19mentioning
confidence: 99%
“…for some other individual urban areas, too [27]. In 2 cities in Morocco, Casablanca and Marrakech, it was estimated that the reduction in PM 2.5 levels contributed to avoiding, respectively, a total of 48 (95% CI: 70-89) and 15 (95% CI: 10-19), deaths related to PM 2.5 exposure during the quarantine period (32 days) [27]. According to recent research, this situation with the improved air quality in Europe saved about 11 000 lives (95% CI: 7000-21 000) only in 1 month [28].…”
Section: Covid-19mentioning
confidence: 99%